2018
DOI: 10.1186/s11658-018-0106-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression and functionality of the gap junction in peripheral blood lymphocytes is associated with hypertension-mediated inflammation in spontaneously hypertensive rats

Abstract: BackgroundImbalances in circulating T lymphocytes play critical roles in the pathogenesis of hypertension-mediated inflammation. Connexins (Cxs) in immune cells are involved in the maintenance of homeostasis of T lymphocytes. However, the association between Cxs in peripheral blood T lymphocytes and hypertension-mediated inflammation remains unknown. This study was designed to investigate the role of Cxs in T lymphocytes in hypertension-mediated inflammation in spontaneously hypertensive rats (SHRs).MethodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…The primary findings of the present study were that β-estradiol significantly prevented inflammation and target organ damage (kidneys and arteries) in male SHRs. Furthermore, while hypertension appears to promote imbalances in the adaptive immune response through increased expression of Cxs (Cx40 and Cx43), which have previously been demonstrated to be pro-inflammatory (1016), β-estradiol appeared to alleviate hypertension-mediated imbalances of the adaptive immune response and T cell mitogenic stimuli-induced adaptive immune response, at least in part, by suppressing the expression of Cxs or the function of Cx gap junctions. β-estradiol inhibited the release of pro-inflammatory cytokines induced by spontaneous hypertension or T cell activation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The primary findings of the present study were that β-estradiol significantly prevented inflammation and target organ damage (kidneys and arteries) in male SHRs. Furthermore, while hypertension appears to promote imbalances in the adaptive immune response through increased expression of Cxs (Cx40 and Cx43), which have previously been demonstrated to be pro-inflammatory (1016), β-estradiol appeared to alleviate hypertension-mediated imbalances of the adaptive immune response and T cell mitogenic stimuli-induced adaptive immune response, at least in part, by suppressing the expression of Cxs or the function of Cx gap junctions. β-estradiol inhibited the release of pro-inflammatory cytokines induced by spontaneous hypertension or T cell activation.…”
Section: Discussionmentioning
confidence: 98%
“…The effect of β-estradiol on the GJIC between peripheral blood lymphocytes was measured using a calcein acetoxymethyl ester (calcein AM) transfer assay as described previously (10,11). Briefly, PBMCs (1×10 6 cells/ml) isolated from WKY rats were incubated in a 6-well plate with a 2.5 µM solution of calcein AM (cat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To create standard curves and regression analysis of mean absorbance, standard cytokine solutions were run in parallel. The optical density at 450 nm was measured for each well using a microtiter plate reader (BP-800; Bioship) and the cytokine concentration was obtained from standard curves of recombinant human IL-2, IL-4 and IFN-γ [35].…”
Section: Cytokine Analysis Via Elisamentioning
confidence: 99%
“…Pneumonia is an inflammatory condition of the lungs, commonly caused by infection and less commonly by other numerous functional abnormalities including immune-functional deficiencies and certain medications [ 161 ]. Both clinical and preclinical studies demonstrated that upregulated gap-junction/hemichannel containing Cx43 and Cx40 in T-lymphocytes were involved in non-infectious pulmonary inflammation [ 162 , 163 , 164 ]. Additionally, the inhibition of the expression and/or function of Cx ( Figure 3 ) [ 162 , 163 , 164 ] improved the proinflammatory reaction via decreasing the proportion of CD4+ T-lymphocytes with the levels of proinflammatory cytokines [ 162 , 163 , 164 , 165 , 166 ].…”
Section: Candidate Pathomechanisms Of Clz Associated With Cx43mentioning
confidence: 99%